Integração multifuncional no desenvolvimento de produtos: estudo de múltiplos casos em indústrias de laticínios mineiras - Silvia Satiko Onoyama (2006)
The innovation of products is gaining attention in managerial and academic atmosphere. The high technological turbulence in the market imposes the development of new products and the constant improvement of the current ones, to assist the consumers' needs in a more efficient way. However, the exercise of the innovation is covered by environment complexity, that includes the consumers' volatile needs, the progress of the technology and the dynamism of the legislation, among other factors. These uncertainties lead to dependencies between and among different functional areas and require inputs and cooperation from different departments, such as Marketing, Production, Research and Development and Quality Control, to accomplish the congruency of innovation management. Under those conditions, this study intended to analyze the multifunctional integration during the development of products in the dairy industry. This study used the multiple cases methodology in four dairy industries located in Minas Gerais State. The data were collected by internal documents analysis and semi-structured interviews with professionals of Marketing, Research and Development, Production and Quality Control departments; and were analyzed by content technique. The obtained results show that, even with the development of already existent products in the market, there is integration among the functional areas. The research detected, that the integration level in Alpha, Beta and Gama companies is reasonable, but there is an agreement that the process can be improved. In Zeta company, the level is considered low, because the integration doesnt involve the Marketing department and the process of the development of new product still needs interventions to professionalize. However, the positive perception of the integration struggles with the limitation of the measurement of integrations efficiency. The companies don't measure the work of each department relating them with the success of the product. It was perceived during the interviews that the product performance measurements orientate the projects of new products, but the companies dont reflect the contribution of each department for the success or failure of the project. For the interviewed people, the integration causes the spread of the information, avoiding rework and releasing mistakes, but these assistances arent considered as indicator of the team performance.